THE EFFECT OF PRICE AND BANK REPUTATION ON CUSTOMER SWITCHING BEHAVIOR OF BANK RAKYAT INDONESIA IN MANADO - Mandagi, Pinkan Elisabeth; Tumiwa, Johan . (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The behavior of switching becoming a serious problem especially in services companies such as bank. The behavior of customers switch banks negatively affect profit and market share. This research was designed to identify the effect of price and bank reputation on customer switching behavior of Bank Rakyat Indonesia in Manado simultaneously and partially. A quantitative method was applied to analyze data collected using convenience sampling. The result of this research showed that price and bank reputation have a significant effect on customer switching behavior of Bank Rakyat Indonesia in Manado simultaneously and partially. Bank Rakyat Indonesia in Manado needs to continue the policies concerning price such as the bank charges, interest for credit and saving, and all of the various of transaction in bank, and always mantain the reputation of bank and financial stability to improve customer trust and loyalty to subscribe and reduce the customer behavior to switch to another bank. Further research is expected to cover larger areas or regions with different demographics, especially in larger cities, so as to be able to see the switching behavior more comprehensively, not just specifically in Manado city, so the results can be compared.Keywords: switching behavior, price, bank reputation